ERKIN VAHIDOV'S ATTITUDE TO THE WORK OF HIS MASTER AND CONTEMPORARY WRITERS IN ART JOURNALISM - Juraev Shukrullo Alishboevich (Academia Science Repository, 2023)
The article analyzes one of the important directions of Erkin Vahidov's artistic journalism, that is, his articles about his teachers and contemporary intellectuals, writers and literary critics, as an example of the article entitled "Drawings of the Teacher's Life", which reflects the work of Ozad Sharafiddinov.